UMKM STRATEGY IN INCREASING INCOME IN THE COVID-19 PANDEMIC TO MAINTAIN BUSINESS CONTINUITY (CASE STUDY ON TRADITIONAL FOOD UMKM KNOW SUMEDANG REGENCY) - Srie Yuniawati, Ayi; Gelar Sudrajat Kusumadinata; Dinda Ayu Firdayanti (SEAN Institute, 2022)
: a small medium micro venture is a class of independent, productive business activities. Besides, people can build it individually and physically in any economic sector. These activities in small medium micro businesses can expand jobs and can provide economic services and can increase overall incomes to communities. At the time of the covid-19 pandemic, many negative effects were on umkm entrepreneurs, especially those with traditional food-related marketing targets for tourists and communities in the area. Many of these entrepreneurs are suffering from incomes and shutting down the business. This study aims to provide more strategies for the increase in revenue generation so that the fund can resume its normal operation and reduce its cost of ending traditional food consumption. Research methods use descriptive methods. The informant identification technique USES a provesive sampling of this data analysis process using the editors and presents the data obtained will then make a withdrawal. The result of this study is to explain that umkm of the traditional food industry known in sumedang district lies in v's cell. for the strategy that must be worked on in the effort to increase revenue to create a sustainable defense against the current covid-19 pandemic of the covid-19 with a way of creating a strategy that utilizes the use of power to The harnessing of these external opportunities.